Population and labour force growth and patterns in ASEAN countries - Swee-Hock, Saw (1988)
The paper shows that the diverse labor dimensions prevailing in the ASEAN region can be attributed to changes in the structure of the society and economy in the course of recent economic development. It observes the considerable variety in the growth of the population and its effect on the labor force in the ASEAN region which has exhibited continuous growth during the last two decades, though at quite different speeds. The paper details the similarity and diversity in the level and type of labor force participation rates. A common feature shared by ASEAN countries is a general pattern in the age-specific participation rate of men. In contrasts, the women, aside from participating in the labor force at a much lower level than men at almost all ages, display diverse patterns of participation over the working age range. Lastly, the distribution of the labor force according to major industrial sectors in the six ASEAN countries is presented, noting the extremely low proportion of 1.6 percent of the labor force in agriculture in Singapore contrasted by Thailand's 72.5 percent, and the similar proportion of the workforce in agriculture in Indonesia and the Philippines.
Keywords: Labor supply; Age and employment